2022
DOI: 10.1029/2022ms003239
|View full text |Cite
|
Sign up to set email alerts
|

A New Halocarbon Absorption Model Based on HITRAN Cross‐Section Data and New Estimates of Halocarbon Instantaneous Clear‐Sky Radiative Forcing

Abstract: The article describes a new practical model for the infrared absorption of chlorofluorocarbons and other gases with dense spectra, based on high‐resolution transmission molecular absorption database (HITRAN) absorption cross‐sections. The model is very simple, consisting of frequency‐dependent polynomial coefficients describing the pressure and temperature dependence of absorption. Currently it is implemented for the halocarbon species required by the Radiative Forcing Model Intercomparison Project. In cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is therefore reasonable that incorporating clouds, will reduce the halogenated gas radiative forcing. Some studies have found clouds reduce the halogenated gas forcing by 25% [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore reasonable that incorporating clouds, will reduce the halogenated gas radiative forcing. Some studies have found clouds reduce the halogenated gas forcing by 25% [7].…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty of the Hitran cross sections is given to be about 8% [7]. Integrating over frequency gave the total cross sections listed in the final column of Table 1.…”
Section: Calculation Of Radiative Forcingmentioning
confidence: 99%
See 1 more Smart Citation
“…HITRAN 883 is a compilation of spectroscopic parameters used by various computer codes to simulate the transmission and emission of light in the atmosphere and derive radiative forcing of aeronomic molecules. 884 HITRAN provides a selfconsistent set of parameters (a mixture of calculated and experimental ones) that are widely adopted by the atmospheric community. Similarly, the fusion community, through IAEA, has developed the ALADDIN database, 885 providing numerical atomic, molecular and plasma-material interaction data of interest to fusion research.…”
Section: Databases For Multiscale Modelingmentioning
confidence: 99%
“…This is particularly true in the atmospheric community where the HITRAN database is used as a standard. HITRAN is a compilation of spectroscopic parameters used by various computer codes to simulate the transmission and emission of light in the atmosphere and derive radiative forcing of aeronomic molecules . HITRAN provides a self-consistent set of parameters (a mixture of calculated and experimental ones) that are widely adopted by the atmospheric community.…”
Section: Databases For Multiscale Modelingmentioning
confidence: 99%